Creating Accessible Chemistry Content for Students with Disabilities: Findings from Schools Providing Inclusive Education in Indonesia - Khafifah Aulia Wulayalin; Jamil Suprihatiningrum (Postgraduate, University of Mataram, 2024)
The trend of students with disabilities attending secondary schools providing inclusive education in Indonesia is rising. This trend requires teachers as a key person to offer learning that suits the needs and abilities of each student, including those with disabilities. This research portrays how chemistry teachers provided alternative modes of representation as one of the principles of Universal Design for Learning (UDL). Three teacher participants from three schools providing inclusive education (SPIE) in the Special Province of Yogyakarta were recruited purposively and agreed to be interviewed on how they varied the chemistry content format. A descriptive method was used and directed content analysis was applied to analyze the data. The findings demonstrated that chemistry learning content were created more accessible for students with disabilities. Three chemistry teacher participants demonstrated that they implemented the principle of Multiple Means of Representation of UDL in a simple manner. The participants created learning objectives without modifying them to suit the student’s abilities. Learning content was offered in various ways and delivered with some strategies. Chemistry teacher participants demonstrated how they provided various assessments to gain students with disabilities opportunities to show their understanding.